Scenario analysis of the long-term impact on energy demand and emissions of B10 use as a clean transport fuel - Tibesigwa, Timothy; Olupot, Peter W.; Kirabira, John B. (Frontiers in Energy Research, 2024)
Sustainable energy sources are continually advocated as the globe strives to transition from non-renewable forms. Energy security risks associated with the gradual depletion of petroleum resources and the related climate change effects require remedies. Nations have enacted laws stipulating biofuel blending mandates to reverse these adverse effects. Using the Low Emissions Analysis Platform (LEAP) software, this study assessed the potential long-term impact on energy demand and CO2 emissions from implementing B10 (10% biodiesel and 90% conventional diesel blend) in Uganda’s petroleum sub-sector was assessed. Four scenarios were analysed from 2019 to 2050: baseline (100% fossil diesel), B10, B20 (20% biodiesel and 80% conventional diesel blend), and electric-powered transport, were analysed for 2019 to 2050. The analysis revealed that replacing fossil diesel with B10 reduces fossil-derived energy demand by 3.52% and projects an 8.38% reduction in CO2 emissions compared to the baseline scenario. The B20 and electric vehicle scenarios offer an even greater reduction. Specifically, the B20 scenario shows an 8.46% decrease, and the electric scenario shows a 9.98% decrease in fossil-derived energy demand. These reductions are attributed to the lower proportion of fossil fuels in biodiesel blends and the higher energy efficiency of electric vehicles. B10 use as a substitute fuel for diesel-powered vehicles is expected to mitigate transport sector emissions in Uganda with minimal impact on final energy demand. B20 and electrification scenarios with lower final energy demand and higher environmental impact reductions are more advantageous relative to the B10 and baseline scenarios. Future analyses should establish the optimal renewable fuel and vehicular technologies mix for a net zero scenario by 2050 for Uganda’s transport sector.